Sobre la historia, distribución y ecología de Veronica tenuifolia subps. fontqueri (Pau) Mart. Ortega & E. Rico en la Sierra de Gádor (Almería, España) - Giménez Luque, Esther; Gómez Mercado, Francisco (Lazaroa, 2001)
Veronica tenuifolia subsp. fontqueri (Pau) Mart. Ortega & E. Rico (= Veronica fontqueri Pau; Veronica rosea Lge. Non Desf.) is a relatively unknown endemic species from Ronda and Cadiz. Since it was described, few studies have contributed information on its distribution and ecology, it having been largely overlooked. During our collecting trips to the Gádor Mountains in recent years, we have confirmed its presence and obtained information on its ecology and distribution in the Gádor massif.